Evaluating Environmental Interpretation with Mixed Method: A Case Study at the International Crane Foundation, Wisconsin. Issue 2 (November 2016) - Ren, Qing; Folta, Elizabeth
A mixed method approach was used to evaluate effectiveness of environmental interpretation on visitors' knowledge, environmental attitude, and pro-environmental behavioral intentions at the International Crane Foundation. Quantitative analysis suggests that participating in personal interpretation has the advantage of improving an audience's knowledge level, but is no more effective than nonpersonal interpretation in influencing attitude and behavioral intentions. Personal and nonpersonal interpretive methods are both effective in promoting knowledge and behavioral intentions for conservation, but do not influence environmental attitude. Qualitative results indicate that participation in personal interpretation makes more of an impression in the visitors' long-term memory than nonpersonal interpretation.